2018
DOI: 10.1186/s12936-018-2524-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of artemisinin-based combination therapy, and molecular markers for artemisinin and piperaquine resistance in Mainland Tanzania

Abstract: BackgroundArtemisinin-based combination therapy (ACT) is the first-line anti-malarial treatment of uncomplicated malaria in most malaria endemic countries, including Tanzania. Unfortunately, there have been reports of artemisinin resistance and ACT failure from South East Asia highlighting the need to monitor therapeutic efficacy of ACT in these countries as recommended by World Health Organization.MethodsOpen-label single arm studies in mainland Tanzania were conducted in nine sentinel sites in 2011, 2012 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 30 publications
20
50
0
Order By: Relevance
“…The results showed high efficacy of ASAQ and AL (microsatellite-corrected D28 efficacies > 99%) to treat uncomplicated malaria, despite their use for more than a decade in Guinea. These results are consistent with the high ACT efficacies observed prior to introduction of ACTs in Guinea and with other studies from Africa [9,[31][32][33][34].…”
Section: Discussionsupporting
confidence: 92%
“…The results showed high efficacy of ASAQ and AL (microsatellite-corrected D28 efficacies > 99%) to treat uncomplicated malaria, despite their use for more than a decade in Guinea. These results are consistent with the high ACT efficacies observed prior to introduction of ACTs in Guinea and with other studies from Africa [9,[31][32][33][34].…”
Section: Discussionsupporting
confidence: 92%
“…The results showed high e cacy of ASAQ and AL (microsatellite-corrected D28 e cacies > 99%) to treat uncomplicated malaria, despite their use for more than a decade in Guinea. These results are consistent with the high ACT e cacies observed prior to introduction of ACT in Guinea and with other studies from Africa [8,11,32,33].…”
Section: Discussionsupporting
confidence: 91%
“…In line with these recommendations, sub-Saharan African countries have initiated the surveillance of the e cacy and safety of anti-malarial drug treatments to prevent parasite resistance [7][8][9][10]. In Tanzania, a study assessing the e cacy and safety of AL for the treatment of uncomplicated Plasmodium falciparum malaria and prevalence of artemisinin resistance molecular markers found high e cacy and safety of AL and no known artemisinin resistance pfk13 mutations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that DHA-PIP drugs were efficacious in treating uncomplicated P. falciparum malaria in the region. This high cure rate of DHA-PIP for Bioko P. falciparum supports earlier findings from and across Africa (16-21). This ACT medicine is being increasingly recommended in malaria endemic countries as second-line treatment for falciparum malaria and also used for mass drug administration in special situations (21).…”
Section: Discussionsupporting
confidence: 88%
“…This high cure rate of DHA-PIP for Bioko P. falciparum supports earlier findings from and across Africa (16-21). This ACT medicine is being increasingly recommended in malaria endemic countries as second-line treatment for falciparum malaria and also used for mass drug administration in special situations (21). However, it was found 5.9% (19/320) patients with D3 positivity, suggesting the possibility that a subset of parasites is becoming less susceptible to ART through mutation in some gene, that some individuals have relatively poor parasite-clearing immune responses, or that some patients were not self-administering their remaining doses of DHA-PIP.…”
Section: Discussionsupporting
confidence: 88%